Pembuatan Website Company Profile pada PT Bridge Marketing Indonesia Sebagai Media Informasi - Yayan Firmansyah (Jurnal Sekretaris dan Administrasi Bisnis, 2024)
PT Bridge Marketing Indonesia is an advertising company and has products in the form of cassava chips and yogurt. Based on the observations, it was stated that in providing information to consumers and public, PT Bridge Marketing Indonesia currently only uses social media in the form of Instagram and does not have its own website yet. This project aims to create an information media for PT Bridge Marketing Indonesia which contains a lot of information in it and can build trust from the public. This project was created using the waterfall method as a website creation design and using WordPress as website content management. The result of this project is a company profile website that can be used for PT Bridge Marketing Indonesia as an information medium. This website includes some information starting from home, about, information, product, contact and there is an order button as a link to the marketplace. This website has been tested for website quality using the webqual method and obtained an average result of 4.432 with very good criteria. It is hoped that this website can continue to be improved both in terms of features and appearance so that it can become an attractive website.